Pengaruh Motivasi Belajar dan Kemampuan Numerik terhadap Prestasi Belajar Akuntansi - Dian Novita (SAP (Susunan Artikel Pendidikan), 2017)
This research aims to show the joint effects of Learning Motivation and Numerical Skill on accounting learning achievement of students of SMA Negeri Jakarta Pusat. If there are positive and significant effects, it can be identified how strong are the effects of learning motivation and numerical skill on accounting learning achievement. The method of the research is a survey with correlation and regression analysis techniques to know the effect of each variable. The sample of the research is students. The statistical description of collected samples are then analyzed and data of requirement test are analyzed before conducting hypothesis test. The secondary data are obtained from school documents, which are scores of Final Test (UAS). From the data analysis and hypothesis test, it can be concluded that: (1) There are jointly significant effects of Learning Motivation and numerical skill on accounting learning achievement of students of SMA Negeri Jakarta Pusat, as shown by the value of sig. 0.000 < 0.05 and FObserved = 93,792 (2) there is a significant effect of Learning Motivation on accounting learning achievement of students of SMA Negeri Jakarta Pusat, as proven by the values of sig. 0.010 < 0.05 and tObserved = 2.673. (3) There is a significant effect of numerical skill on accounting learning achievement of students of SMA Negeri Jakarta Pusat, as seen by the value of sig. 0.000 < 0.05 and t Observed= 4.929.